2011
DOI: 10.1186/1471-2350-12-130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic analyses of three Korean families with hereditary hemorrhagic telangiectasia

Abstract: BackgroundHereditary hemorrhagic telangiectasia (HHT) is an autosomal-dominant vascular disorder, characterized by recurrent epistaxis, mucocutaneous telangiectases, and arteriovenous malformations (AVMs) in various visceral organs. Endoglin (ENG) and activin receptor-like kinase 1 (ACVRL1; ALK1), receptors for transforming growth factor-β (TGF-β) superfamily, have been identified as the principal HHT-causing genes.MethodsThree unrelated Korean HHT patients and their asymptomatic as well as symptomatic family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 31 publications
7
25
0
Order By: Relevance
“…These findings clearly suggest that non-coding regions may also play a role in the disease. In fact, several reports have described the existence of HHT causing mutations in the 5'UTR and introns of ENG [http://arup.utah.edu/database/ ENG/ENG_display.php; [16,17,[19][20][21]. Among these are variants that involve the 400-bp upstream from the TIS of ENG, a region near the transcription initiation site and essential for ENG promoter function [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings clearly suggest that non-coding regions may also play a role in the disease. In fact, several reports have described the existence of HHT causing mutations in the 5'UTR and introns of ENG [http://arup.utah.edu/database/ ENG/ENG_display.php; [16,17,[19][20][21]. Among these are variants that involve the 400-bp upstream from the TIS of ENG, a region near the transcription initiation site and essential for ENG promoter function [18].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in some of these families have revealed the existence of mutations in non-coding DNA sequences such as introns or regulatory regions of ENG [http://arup.utah.edu/database/ENG/ENG_display.php; [16,17]. In this sense, mutations in the 5'UTR of ENG [18] may account for the pathogenesis of HHT in some patients [19][20][21]. Supporting the critical regulatory role of this region is the fact that most of the protein complexes involved in transcription and/or translation bind and regulate expression from the 5'UTR of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…No mutation was identified in 12 probands, which can be explained in different ways. Mutations may reside outside the coding sequence, in introns, in the promoter , or in other regulatory regions. As linkage analysis has already pointed out also other, yet unidentified, genes could be responsible for the HHT phenotype in some families.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations range from single base-pair changes to major deletions of multiple exons. Recently, pathogenic mutations affecting the 5’ UTR region of ENG leading to new translation initiation sites (TIS) dominant over the normal endoglin TIS have also been described [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%